Righteous kill - Avnet, Jon, 1949-; Cowan, Rob.; Davidson, Boaz, 1943-; Emmett, Randall; Furla, George; Grobman, Lati.; Lerner, Avi.; Milchan, Alexandra; Rosenberg, Daniel M.; Gewirtz, Russell; De Niro, Robert; Pacino, Al, 1940-; et al. ([Burbank, CA] : Anchor Bay Entertainment, 2009)
Turk and Rooster are two aging NYPD detectives who have been partners for 30 years. They are faced with a serial killer who is murdering other sociopathic criminals. They both have personal issues. They start working with Perez and Riley, a younger team. Tensions between the pairs of partners is inevitable, especially since Turk is now living with Perez's ex-girlfriend. She also happens to be a homicide detective. But before Turk and Rooster can retire, they are called in to investigate the murder of a notorious pimp, which has ties to a case they solved years before.
DVD; Dolby Digital.
Robert De Niro, Al Pacino, Curtis Jackson, Carla Gugino, John Leguizamo, Donnie Wahlberg, Brian Dennehy.
Director of photography, Denis Lenoir ; editor, Paul Hirsch ; music, Edward Shearmur.
Originally released as a motion picture in 2008.
Widescreen.
MPAA rating: R; for violence, pervasive language, some sexuality and brief drug use.
Keywords: Detectives -- New York (State) -- New York -- Drama; Serial murderers -- New York (State) -- New York -- Drama; Homicide investigation -- New York (State) -- New York -- Drama; Criminal behavior -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama